2019
DOI: 10.1016/j.euf.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy Between European Association of Urology Guidelines and Daily Practice in the Management of Non–muscle-invasive Bladder Cancer: Results of a European Survey

Abstract: Our survey among European physicians investigated discrepancies between guidelines and daily practice in the management of non-muscle-invasive bladder cancer (NMIBC). We conclude that the use of the recommended diagnostic tools, risk-stratification of NMIBC, and performance of re-TURB have been adopted, but adjuvant intravesical treatment and follow-up are not uniformly applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
44
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 22 publications
8
44
1
3
Order By: Relevance
“…A recent literature review summarized available evidence from multinational studies regarding adherence to AUA, Society of Urologic Oncology, and EAU guidelines for NMIBC and found poor compliance regarding repeat TURBT for high-risk tumors (range 28-43%) [7]. We showed repeat TURBT rates of 77.5%, which mirrors recent findings from a large-scale multinational European survey study, reporting 80% of surveyed urologists advocating a repeat TURBT in the high-risk setting [5]. In our study, the poorest guideline compliance within the 3 metrics was observed for adjuvant instillation therapy with only 62.2% of patients receiving adequate subsequent treatment.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…A recent literature review summarized available evidence from multinational studies regarding adherence to AUA, Society of Urologic Oncology, and EAU guidelines for NMIBC and found poor compliance regarding repeat TURBT for high-risk tumors (range 28-43%) [7]. We showed repeat TURBT rates of 77.5%, which mirrors recent findings from a large-scale multinational European survey study, reporting 80% of surveyed urologists advocating a repeat TURBT in the high-risk setting [5]. In our study, the poorest guideline compliance within the 3 metrics was observed for adjuvant instillation therapy with only 62.2% of patients receiving adequate subsequent treatment.…”
Section: Discussionsupporting
confidence: 73%
“…Given the greater propensity of progression in patients with tumors invading the subepithelial connective tissue (pT1), the current gold standard treatment for this stage includes repeat TURBT and intravesical instillation therapies, whereas even early cystectomy can be considered in therapy refractory cases [4]. Worldwide, appropriate observations have been made regarding poor guideline adherence during the treatment of patients with NMIBC [5][6][7][8]. Against this backdrop, our aim was to mirror contemporary guideline adherence focusing on pT1 NMIBC and to evaluate patients from 4 German institutions.…”
mentioning
confidence: 99%
“…Second TURBT (re-TURBT) was performed by the same urologist who performed the first TURBT within 6 wk [8]. The re-TURBT protocol included resection of the tumor scar and base, together with the bladder neck (for CIS) and red bladder patches.…”
Section: Patient Populationmentioning
confidence: 99%
“…Bladder cancer (BC) is the fourth most commonly diagnosed cancer in men and the eighth most lethal [1]. Optimal detection and surveillance of BC rely primarily on the cystoscopic visualization and accurate documentation of all bladder lesions [2,3]. There are presently two main drawbacks associated with the current diagnostic approach.…”
Section: Introductionmentioning
confidence: 99%